REDUKSI MAKNA KAFA’AH PADA GEN-Z : PERSPEKTIF SOSIO-HUKUM ISLAM DI ERA MEDIA SOSIAL - Lina Amalia; Andi Iswandi (UAS PRESS, 2026)
The shifting meaning of kafa’ah among Generation Z has become increasingly evident amid the strong influence of social media as a space for shaping values and partner preferences. This study aims to analyze how Gen Z understands and reinterprets the concept of kafa’ah in marriage and to assess its alignment with classical fiqh through a socio-legal Islamic perspective. Employing a qualitative socio-legal approach with a descriptive-analytic design, this research integrates library research with fieldwork through social media content observation, interviews, and documentation. The findings indicate a significant reduction in the classical meaning of kafa’ah among Generation Z. While classical fiqh traditionally emphasizes religion and morality, Gen Z’s interpretation has shifted toward socio-economic considerations, digital aesthetics, lifestyle compatibility, and visual standards reinforced by TikTok, Instagram, and other social media platforms. Phenomena such as the “Marriage is Scary” narrative, the normalization of consumeristic ideals for partners, and critiques of conventional gender relations contribute to the formation of new perspectives in Gen Z’s partner selection. Although some members of Gen Z still consider religious aspects, the majority tend to interpret kafa’ah more flexibly by prioritizing equality, communication, and emotional readiness. This study concludes that Gen Z’s reinterpretation of kafa’ah does not fully align with classical fiqh, yet it can be understood as a response to rapid socio-cultural changes in the digital era. Therefore, a maqāṣid al-sharī‘ah–based recontexualization of kafa’ah is needed to ensure its continued relevance without undermining the foundational Islamic values of building a harmonious family.